Sustainability of Local Products: Interest to Buy, Product Quality and Promotion - Hermawan, Eric (Dinasti Publisher, 2021)
Through the MSME sector, local products are the drivingdsfs force of a country's economy. During this era of disruption, it becomes a challenge for business actors to realize sustainability and improve the image of local products. Some indicators increase the opportunity for local products to compete, namely buying Interest, product quality, and promotion. For this reason, business actors need to pay attention to these three indicators to improve their competitive strategy for local products. This research uses a descriptive qualitative method by collecting data through Google Scholar and using Mendeley as a reference. The results of this study are: 1) Buying Interest plays a role in the sustainability of local products, 2) product quality plays a role in the sustainability of local products, and 3) promotion plays a role in the sustainability of local products.